Students' critical thinking skills on human respiratory system material in flipped classroom - Elsa Cenora Simatupang; Melva Silitonga; Sri Handayani Rajagukguk (University of Muhammadiyah Malang, 2023)
The learning process must actively involve students and provide opportunities for them to improve their critical thinking skills. This study determines the effect of the implementation flipped classroom on the critical thinking skills of students in the learning of the human respiratory system in class XI SMAN 16 Medan. This study included a quasi-experiment type with one group pretest-posttest design and was conducted in three meetings. The research instrument used is an essay test of 5 questions. Data obtained from this study include the value of students' critical thinking skills both in general and in each indicator, and the N-gain of students' critical thinking ability. The data obtained were analyzed to obtain an average value. The results of the data analysis showed that the average score of students' critical thinking skills in general increased from 39.6 before learning was carried out to 80.8 after learning was carried out. The average student score gets an N-gain score of 0.68 with the moderate improvement category. The average score of students after learning on each indicator is as follows: the basic classification indicator is in the high category (74), basic support is in the very high category (92), inference is in the high category (75), advance classification is in the high category (75), and strategy and tactics is in the very high category (88). Based on the results of the study, the flipped classroom learning model can improve the critical thinking skills of grade XI students in SMAN 16 Medan in learning the biology of the human respiratory system material.